2019
DOI: 10.1002/esp.4607
|View full text |Cite
|
Sign up to set email alerts
|

Investigating dune‐building feedback at the plant level: Insights from a multispecies field experiment

Abstract: Coastal foredunes provide the first line of defense against rising sea levels and storm surge and for this reason there is increasing interest in understanding and modeling foredune formation and post‐storm recovery. However, there is limited observational data available to provide empirical guidance for the development of model parameterizations. To provide guidance for improved representation of dune grass growth in models, we conducted a two‐year multi‐species transplant experiment on Hog Island, VA, U.S.A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 72 publications
(188 reference statements)
1
15
0
Order By: Relevance
“…The high-resolution terrestrial lidar measurements collected in this study demonstrate the important role of dune grasses on trapping wind-blown sediment and its potential beneficial use in dune management. Consistent with numerous other works (e.g., [65,[88][89][90]), grass planting may be an effective measure in limiting aeolian transport to homes adjacent to the beach and enhancing coastal resilience to flooding by promoting natural dune growth (Figures 9, 10 and 12). However, morphological feedbacks similarly have an important role in influencing dune dynamics ( Figures 7, 8 and 13).…”
Section: Implications For Managementsupporting
confidence: 86%
“…The high-resolution terrestrial lidar measurements collected in this study demonstrate the important role of dune grasses on trapping wind-blown sediment and its potential beneficial use in dune management. Consistent with numerous other works (e.g., [65,[88][89][90]), grass planting may be an effective measure in limiting aeolian transport to homes adjacent to the beach and enhancing coastal resilience to flooding by promoting natural dune growth (Figures 9, 10 and 12). However, morphological feedbacks similarly have an important role in influencing dune dynamics ( Figures 7, 8 and 13).…”
Section: Implications For Managementsupporting
confidence: 86%
“…Spartina patens shoots were also relatively short and very thin compared to the other species, likely explaining the lower sand accretion values similar to P. amarum and U. paniculata (Figure 8). Interestingly, a recent field experiment by Mullins et al [37] demonstrated that although S. patens is less efficient in accreting sand than A. breviligulata and U. paniculata, it, too, functions as a dune builder, contrary to previous thought [38,39].…”
Section: Species-specific Functional Morphology and Associated Changementioning
confidence: 86%
“…Previous studies have demonstrated that the engineering ability of species can be related to its species‐specific expansion strategy (Hacker et al ., 2012; Bouma et al ., 2013; Schwarz et al ., 2018; Mullins et al ., 2019; Reijers et al ., 2019b). However, so far in the field of ecosystem‐engineering and biogeomorphology, engineering traits have been mostly considered as invariant properties of species, even though intraspecific variability and environment‐dependent trait expression can have far‐reaching consequences for ecosystem dynamics and functioning (Hughes & Stachowicz 2004, de Battisti et al 2020).…”
Section: Discussionmentioning
confidence: 99%